A sensor array for the discrimination of polycyclic aromatic hydrocarbons using conjugated polymers and the inner filter effect. Issue 44 (14th October 2019) - Tropp, Joshua; Ihde, Michael H.; Williams, Abagail K.; White, Nicholas J.; Eedugurala, Naresh; Bell, Noel C.; Azoulay, Jason D.; Bonizzoni, Marco
Abstract : The inner filter effect and multivariate array sensing using conjugated polymers are combined for the detection and challenging discrimination of closely related polycyclic aromatic hydrocarbons. Abstract : Natural and anthropogenic activities result in the production of polycyclic aromatic hydrocarbons (PAHs), persistent pollutants that negatively impact the environment and human health. Rapid and reliable methods for the detection and discrimination of these compounds remains a technological challenge owing to their relatively featureless properties, structural similarities, and existence as complex mixtures. Here, we demonstrate that the inner filter effect (IFE), in combination with conjugated polymer (CP) array-based sensing, offers a straightforward approach for the quantitative and qualitative profiling of PAHs. The sensor array was constructed from six fluorescent fluorene-based copolymers, which incorporate side chains with peripheral 2-phenylbenzimidazole substituents that provide spectral overlap with PAHs and give rise to a pronounced IFE. Subtle structural differences in copolymer structure result in distinct spectral signatures, which provide a unique "chemical fingerprint" for each PAH. The discriminatory power of the array was evaluated using linear discriminant analysis (LDA) and principal component analysis (PCA) in order to discriminate between 16 PAH compounds identified as priority pollutants by the US Environmental Protection Agency (EPA). This array is the first multivariate system reliant on the modulation of the spectral signatures of CPs through the IFE for the detection and discrimination of closely related polynuclear aromatic species.